2023
DOI: 10.3390/fishes8050261
|View full text |Cite|
|
Sign up to set email alerts
|

Parasitic Copepods as Biochemical Tracers of Foraging Patterns and Dietary Shifts in Whale Sharks (Rhincodon typus Smith, 1828)

Brendon James Osorio,
Grzegorz Skrzypek,
Mark Meekan

Abstract: Understanding the diet of whale sharks (Rhincodon typus) is essential for the development of appropriate conservation strategies for the species. This study evaluated the use of the parasitic copepod (Pandarus rhincodonicus) as a proxy to infer short-term foraging habitats and trophic positions of whale shark hosts. To accomplish this, bulk stable carbon (δ13C) and nitrogen (δ15N) isotope compositions were analysed from 72 paired samples of whale shark skin (dermal) tissues and copepods collected across six ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Other studies have also found a close association between horizontal (2D) movement patterns of whale sharks and their prey at scales of 1–10 s of kilometres, particularly where whale sharks aggregate to feed on prey originating from a limited source area such as spawning schools of fishes [ 28 , 65 ] or krill swarms [ 29 , 66 ]. The core area of use by whale sharks at Ningaloo Reef was directly adjacent to a large reef passage slightly south of Point Cloates and is a predictable “hotspot” of whale shark abundance, with high numbers recorded there over many years [ 67 , 68 ]. The presence of these dense water pockets also supports larger-scale studies of reef passages at Ningaloo, where oceanographic frontal zones due to physical forcing mechanisms (e.g., tides, waves and wind) flush more dense lagoon water towards the shelf where it mixes with shelf water and enhances productivity [ 45 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found a close association between horizontal (2D) movement patterns of whale sharks and their prey at scales of 1–10 s of kilometres, particularly where whale sharks aggregate to feed on prey originating from a limited source area such as spawning schools of fishes [ 28 , 65 ] or krill swarms [ 29 , 66 ]. The core area of use by whale sharks at Ningaloo Reef was directly adjacent to a large reef passage slightly south of Point Cloates and is a predictable “hotspot” of whale shark abundance, with high numbers recorded there over many years [ 67 , 68 ]. The presence of these dense water pockets also supports larger-scale studies of reef passages at Ningaloo, where oceanographic frontal zones due to physical forcing mechanisms (e.g., tides, waves and wind) flush more dense lagoon water towards the shelf where it mixes with shelf water and enhances productivity [ 45 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ultrasound scanning, the ability to arrest the forward motion of whale sharks by invoking a cleaning response may provide other opportunities for sampling. Parasite collections can provide information on the DNA (Meekan et al, 2017) and recent diet of the whale shark host (Osorio et al, 2023). It may also provide opportunities to collect samples of the shark microbiome and eDNA (Dugal et al, 2022) and to attach, adjust or remove biologging and satellite tags from fins.…”
Section: Discussionmentioning
confidence: 99%
“…The divers photographed the left and right flanks for photo-identification of individuals (Meekan et al, 2006;Speed et al, 2007), recorded the shark using underwater stereo-video for later measurement of body size (Sequeira et al, 2016) and sampled tissue biopsies for genetic studies (Meenakshisundaram et al, 2021;Dugal et al, 2022). Parasitic copepods were then collected from the shark for genetic and isotopic studies (Meekan et al, 2017, Meekan et al, 2022Osorio et al, 2023). These copepods were scraped from the lips and leading edges of the pectoral fins and the ventral surface towards the mouth using a plastic knife by a snorkeler swimming alongside the unrestrained shark (Meekan et al, 2017).…”
Section: Study Site and Sampling Techniquementioning
confidence: 99%